CONCEPTUALIZING ECO-GASTRONOMY FOR SOCIO-ECOLOGICAL RESILIENCE: THE CASE OF BALI, INDONESIA - Bondan Pambudi; I Made Darsana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Bali’s tourism economy has become increasingly vulnerable to ecological degradation and disasters such as the 2025 Bulana Lau flood and landslide. This study examines how eco-gastronomy, the integration of food culture, ecology, and sustainability ethics, can serve as a framework for fostering ecological and social resilience. Methods:A qualitative, interpretive design was employed using a library-based analytical approach. Literature, institutional reports, and contextual data from the Bulana Lau disaster were analyzed through conceptual mapping, cross-regional comparison, and analytical generalization informed by resilience theory and Tri Hita Karana philosophy. Results Findings show that eco-gastronomy strengthens resilience through five mechanisms: environmental stewardship, economic diversification, social capital, adaptive innovation, and equitable benefit distribution. Upland Bangli communities illustrate stronger adaptive capacity than Bali’s coastal mass-tourism areas. Discussion and Conclusion Eco-gastronomy in Bali forms a hybrid model of cultural–ecological resilience aligned with SDGs 2, 11, 12, and 13, offering a transferable framework for sustainable tourism and environmental recovery.